Upaya Peningkatan Performa Supplier PT. FSCM Manufacturing Indonesia - Gabriel Firdaus Soediono (Jurnal Titra, 2018)
This research was conducted to reduce the percentage of sorting and return to the supporting material submitted by supplier PT. FSCM manufacturing Indonesia plant 4. The supporting material that has a sorting and return description will cause product can’t send to the customer. The effort in reducing the percentage of sorting and return can be done by way of analyzing the problems on the supporting material. The methods used in conducting the analysis of the causes is 5 why analysis, searching for every little problems. The results of the analysis will be a reference in making a work instruction and inspection instruction to each process in problems in the supplier. Work instruction and inspection instruction will be through the verification first before being implemented by the supplier. The results of the implementation will be compared with the percentage of sorting and return before the implementation of the work instruction and inspection instruction. The results of this study showed a decrease in the percentage of sorting and return inner box 2,63%, outer box 2,53%, dan packing 0,64%.